Directive Skills in the Investment Cycle of a Peruvian Public Entity from 2019 to 2022 - Pérez-Mamani, Rubens Houson; Miranda, Ofelia Carol Cernaque; Cuela, Fausto Enrique Prudenci; Camones, Carlos Heraclides Pajuelo; Contreras, Segundo Manuel Alvarado; Benavides, Elmer Oswaldo Barrera (Migration Letters, 2023)
The objective of the research is to determine how directive skills influence the investment cycle in a public entity in Peru, from 2019 to 2022. The study is of an applied, explanatory level, with a non-experimental design, with a population of 317 workers and a sample of 174. The technique employed was the survey, and the instrument was the questionnaire, using the judgment of six experts for its validation, with a Cronbach’s alpha of 0.951 for “Directive skills” and 0.912 for “Investment cycle”, and the approach is quantitative. It was obtained that 71.3% of the personnel perceive management skills as regular, where the most outstanding dimension was “Personal level skills” and the one with the lowest rating was “Direction level skills”; and 86.2% perceive the implementation of the investment cycle as regular, where the most outstanding dimension was “Execution” and the one with the lowest rating was “Functioning”. It was concluded that the directive skills of the officers influence the investment cycle, where the result of the ordinal logistic regression gave a chi-square = 38.929 (p = 0.000), and an R2 Nagelkerke = 31.8%.